Assessing the needs of older people in urban settings: integration of emotive, physiological and built environment data. Issue 1 (22nd June 2017) - Walford, Nigel; Phillips, Judith; Hockey, Ann; Pratt, Susan
Abstract : This article shows the results of combining walkability and urban design audit data with physiological measures and coded oral narratives in order to provide a holistic assessment of unfamiliar urban environments by older people. It uses spatial analysis techniques to identify and visualise hot and cold spots around a circular walking route. e00037 Abstract : Design of the built environment for navigability and walkability is an increasingly important aspect of urban planning. This focus derives in part from increasing interest in lifestyles and behaviours, including level of physical activity and health outcomes. Geographical information systems and virtual realities are playing a significant role in advancing this agenda: examples exist of integrating qualitative data (words about or visual images of places) and quantitative data (numerical descriptions of places). However, there remain opportunities for exploring alternative ways of linking different types of data (physiological measurements, emotional response, street walkability and urban design quality) to address issues of urban planning and renewal. Using a case study approach this paper explores the application of geographic information science and systems to participatory approaches in built environment planning with the aim of exploring older people's response to an unfamiliar urban environment. It examines different ways of combining temporally and spatial referenced qualitative and quantitative data. The participants in the study were a group of 44 older people (60+) from Swansea, Wales, who viewed a filmed walking route around Colchester, England. While viewing the film they gave an oral commentary and physiological readings were made, which have been integrated with primary data collected on the built environment along the walking route. Proximity and inverse distance weighting approaches for combining these datasets produce complementary results in respect of older people's physiological and emotive response to variation in the walkability and design quality of a walking route through an unfamiliar town centre. The results reveal participants experienced an elevated average heart rate close to Colchester Town railway station and expressed a comparatively negative emotional response to this location. Conversely participants experienced lower average heart rate, indicating reduced stress, in Brook Street where the overall Urban Design Quality score was relatively low.